Realising Violent Extremist Risk Assessments in Indonesia: Simplify and Collaborate - Cameron Sumpter (Journal for Deradicalization, 2020)
Evaluations aiming to assess the risk posed by individuals suspected or convicted of violent extremist activity have developed rapidly since the late 2000s. Largely based on a process known as structured professional judgement, terrorist risk assessments have drawn upon decades of research on those used for non-ideological violent criminals, and inserted contemporary understandings of what may drive extremist violence. While uncertainty over precise risk factors presents ongoing challenges, the primary problem is that risk assessment instruments tend to be time consuming and complex, thus requiring a level of practitioner expertise not always readily available. Over the past several years, Indonesia has been experimenting with strategies to evaluate risk among individual extremist prisoners, but disagreements over suitability and human resource constraints have hindered progress. One way forward could be the establishment of a more simplified assessment system shared by relevant government stakeholders, from law enforcement to prison authorities to social service providers. While an abridged judgement process would hold limited capacity for prediction, a collaborative approach would add clarity and much needed inter-agency coordination to the management of convicted extremists in Indonesia.